STRATEGI KOMUNIKASI HUTNAS PEMERINTAHAN KABUPATEN BENGKALIS DALAM MENSOSIALISASIKAN PILKADA SERENTAK TAHUN 2015 - Handayani, Sri; Awza, Rusmadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
study was conducted to determine and analyze to identify their communication, communication media selection, assessment, communication and the role of interest komunitor role in communication for PR communications strategy Bengkalis district administration in disseminating election outright in 2015. The formulation of the problem in this research is how to identify their communication, the selection of communication media, the role of communication and assessment purposes komunitor role in communication for PR communications strategy Bengkalis district administration in disseminating election outright in 2015.This research is a descriptive study using a qualitative approach as a tool of analysis. This research was conducted at the Government Public Relations Office, Bengkalis District, which is the executing agency where elections simultaneously in 2015. The sample in this research that Government Relations and Community Leaders Bengkalis Bengkalis which amounted to 7 people. Data collection techniques of observation, interviews and documentation.The results of the study are from the introduction of targeted communication is known that prior to socialize elections simultaneously in Bengkalis then conducted the meeting in order to plan socialization which will be held as well as the objects that will be addressed, from the selection of media communication is done by making flyers or pamphlets about the elections simultaneously, from assessment purpose communication message known to the parties involved in the implementation of the socialization of the elections in Bengkalis should focus primarily on delivering the objectives of socialization and of the role of communicators in communication can be seen from the positive impact resulting in socialization election simultaneously in Bengkalis which all parties concerned can carry out their duties in accordance with the functions that have been set before socialization.